MANAJEMEN MUTU PRODUK HORTIKULTURA DI HYPERMART PEKANBARU - Tengku Harunur Rasyid; Yeni Kusumawaty (Fakultas Pertanian, Universitas Riau, 2018)
The presence of today's modern market has offer a complete shopping place known as the concept of